T lymphocyte phenotype of contact‐allergic patients: experience with nickel and p‐phenylenediamine. (8th April 2019) - Wicks, Kate; Stretton, Clare; Popple, Amy; Beresford, Lorna; Williams, Jason; Maxwell, Gavin; Gosling, John Paul; Kimber, Ian; Dearman, Rebecca J.
Abstract : Background: There is considerable interest in understanding the immunological variables that have the greatest influence on the effectiveness of sensitization by contact allergens, particularly in the context of developing new paradigms for risk assessment of novel compounds. Objectives: To examine the relationship between patch test score for three different contact allergens and the characteristics of T cell responses. Methods: A total of 192 patients with confirmed nickel, p ‐phenylenediamine (PPD) or methylisothiazolinone (MI) allergy were recruited from the Contact Dermatitis Investigation Unit at Salford Royal Hospital. Severity of allergy was scored by the use of patch testing, peripheral blood lymphocytes were characterized for T cell phenotype by flow cytometry, and proliferative activity was characterized by radiolabelled thymidine incorporation. Comparisons were drawn with buffy coat samples from healthy volunteers. Results: Patch test positivity for nickel, PPD and MI was associated with changes in the phenotype of peripheral blood T cells: increases in naïve cells, decreases in regulatory T cell frequency and the CD4 + /CD8 hi ratio, and increased expression of the skin‐homing marker cutaneous lymphocyte antigen (CLA), particularly for those patients with a +++ patch test score. Conclusions: This increased understanding of the characteristics of the T cell responses to contact allergens may provide parameters with which to better measure health risks associated with skin sensitization.